Nesprin-2 Interacts with Condensin Component SMC2 - Xin Xing; Carmen Mroß; Linlin Hao; Martina Munck; Alexandra Herzog; Clara Mohr; C. P. Unnikannan; Pranav Kelkar; Angelika A. Noegel; Ludwig Eichinger; Sascha Neumann (International Journal of Cell Biology)
The nuclear envelope proteins, Nesprins, have been primarily studied during interphase where they function in maintaining nuclear shape, size, and positioning. We analyze here the function of Nesprin-2 in chromatin interactions in interphase and dividing cells. We characterize a region in the rod domain of Nesprin-2 that is predicted as SMC domain (aa 1436–1766). We show that this domain can interact with itself. It furthermore has the capacity to bind to SMC2 and SMC4, the core subunits of condensin. The interaction was observed during all phases of the cell cycle; it was particularly strong during S phase and persisted also during mitosis. Nesprin-2 knockdown did not affect condensin distribution; however we noticed significantly higher numbers of chromatin bridges in Nesprin-2 knockdown cells in anaphase. Thus, Nesprin-2 may have an impact on chromosomes which might be due to its interaction with condensins or to indirect mechanisms provided by its interactions at the nuclear envelope.